2007
DOI: 10.1002/jor.20381
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of metal‐on‐metal total hip replacement

Abstract: Metal-on-metal articulations were reintroduced to reduce polyethylene particleinduced osteolysis. Elevated serum metal levels have been detected at short-and intermediateterm follow-up. There is little knowledge about long-term effects of increased ionic metal generation. Our study was undertaken to provide information about long-term survival, clinical outcome, radiographic appearance, and serum metal concentrations after a minimum 10 years follow-up with a metal-on-metal hip prosthesis: 105 cementless primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 33 publications
8
69
1
4
Order By: Relevance
“…Observations on MOM THAs with 28-and 32-mm articulations have been extensively reported [13,18,19,21,29,43,46,47]. Some authors have noted intermediate Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…Observations on MOM THAs with 28-and 32-mm articulations have been extensively reported [13,18,19,21,29,43,46,47]. Some authors have noted intermediate Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported good results with the Metasul at followup of more than 10 years with survival ranging from 81% to 100% (Table 2) [10,12,15,20,22,35,42,43,45]. Two other studies have reported mid-to long-term followup for small-diameter MoM THA devices other than Metasul [36,39].…”
Section: Discussionmentioning
confidence: 99%
“…A contraindication for use of MoM devices was in patients known to have renal insufficiency, as recommended in some studies [7,15,32,33]. Use of MoM devices gradually shifted from small-diameter head devices to larger diameter head devices, which were touted to provide greater stability as the large head designs became available with no change in indications.…”
Section: Methodsmentioning
confidence: 99%
“…In well‐functioning prostheses at 10‐year follow‐up, median Co and Cr concentrations in the circulation have been reported to be 0.75 μg/L (range: 0.3–50.1 μg/L) and 0.95 μg/L (range: 0.3–58.6 μg/L) respectively 17. Periprosthetic concentrations are several fold higher (median Co, 113 μg/L; median Cr, 54 μg/L),18 while patients with failing prosthesis have reported Co and Cr concentrations as high as 528 μg/L (range: 0–13,000 μg/L) and 1,844 μg/L (range: 0–38,600 μg/L), respectively 19.…”
mentioning
confidence: 99%